Report of two pediatric cases of allergic contact dermatitis induced by temporary henna tattoos. - Pedicelli, C.; Provini, A.; Cacciaguerra, M.G.; Stella, P.; Paradisi, M. (European Journal of Pediatric Dermatology, 2003)
In the last few years, the henna tattoo fashion has widely spread throughout the Westerncountries. We report two cases of allergic contact dermatitis observed in children afterpaint on henna tattoo procedures. The patients came to our outpatients’ clinic for the onsetof erythematous and edematous, pruriginous lesions where the skin had been tattooed 3 weeks before. Treatment with topical steroids and systemic antihistamines led to theregression of the symptoms. Later, European Standard Series Patch Tests were positive in both cases for paraphenylenediamine (PPD) at 1%. We point out the young age of our twopatients (7 years) and the need to inform the public on the risks of this sensitization, due tothe widespread custom of this procedure.